Influence of cost stickiness on return prediction in companies listed on B3 - Costa, Laura Brandão; Tavares, Marcelo (Advances in Scientific and Applied Accounting, 2025)
Objective: To evaluate the accuracy of return forecasts for investors in companies listed on B3, considering the asymmetric behavior of costs. Method: A quantitative analysis was conducted using the financial statements of 103 companies over the period from 2010 to 2022, with data obtained from Economatica®. Econometric models were employed to identify the presence of cost stickiness and to examine its relationship with return predictability. Results: Evidence of cost stickiness was observed among the firms analyzed, suggesting a prevailing optimism in the Brazilian market. This is based on the premise that companies are more inclined to allocate additional resources rather than reduce them, implying that expenditures are often made in anticipation of positive demand conditions. Both the presence and higher degrees of cost stickiness were found to be negatively associated with the predictability of future returns, thereby indicating that models incorporating this phenomenon may offer greater forecasting accuracy. Contributions: This study underscores the importance of disclosing cost stickiness to capital market participants, as it may enhance their understanding of cost structure dynamics and their implications for the growth of operating assets and future revenue generation. Such insights contribute to a more robust interpretation of financial statements, particularly with respect to return forecasting.